Program Peningkatan Minat Belajar Anak Melalui Kegiatan Bimbingan Belajar Berkelas Dan Gratis Bersama Mahasiswa Kkn Desa Air Lintang - Fajar, Ayu (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
Education stands as a fundamental pillar in fostering a progressive and competitive society. However, the challenges faced by the Indonesian education system, particularly in remote and rural areas like Desa Air Lintang, remain significant. Low student interest, hindered by limited access to learning resources, insufficient motivation, and minimal environmental support, pose a major obstacle. To address this issue, the KKN-MB IAIN Syaikh Abdurrahman Siddik Bangka Belitung 2024 Group 02 launched the "Bingkisan: Free and Class-Based Learning Guidance" program. This program aimed to enhance student interest in learning through engaging and inspiring academic guidance, encompassing a variety of subjects and languages. It also eliminated financial barriers that often impede access to supplementary education. Employing interactive teaching methods, rewards, and individualized guidance, the program effectively boosted student motivation and academic understanding, provided equitable access to education, and cultivated a strong passion for learning. Evaluation results demonstrated a significant improvement in the comprehension and learning interest of participating children.